Miliaria crystallina-congenital form; a rare but benign entity – A case report - Biswas, Biswajit; Arka Karmarkar; Krishnendu Bandyopadhyay; Sayan Chatterjee; Subrata Ghosh; Rohit Ishan; Subhadeep Bag; Naman Sankhala; Atreyee Sinha; Chayanik Ghosh; et al. (Asian Journal of Medical Sciences, 2025)
Miliaria results from blockage of eccrine sweat ducts with leakage into epidermis or dermis. Miliaria crystallina (MC) is a distinct form presenting mostly in newborns younger than 2 weeks. Congenital (i.e., present at birth) MC is extremely rare. Very few cases have been reported till date. We report on such a case where mother apparently did not have any complication during pregnancy or at the time of childbirth. This is a very benign condition, but it closely mimics some serious skin infections and vesiculo-bullous eruptions at this age.